Pengaruh Kualitas Auditor Internal dan Efektivitas Komite Audit terhadap Korupsi Di BUMN - Luh Wulan Permatasari; Poppy Sofia Koeswoyo; Cahya Irawady (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims at examining the effect of quality of internal auditors and the effectiveness of audit committees on corruption in State-Owned Enterprises (SOE). The quality of the internal auditors is proxied by the competence (experience, certification, training) and objectivity of the internal auditors. Meanwhile, the audit committee is proxied by size, independence, number of meetings, and expertise of the audit committee. The research method used is a quantitative method with the type of hypothesis testing research. The population of this study were state-owned enterprises listed on the Indonesia Stock Exchange (IDX) in 2016 - 2020. Sampling used purposive sampling and obtained a sample of 20 companies with a total of 100 observations over 5 years. This study uses secondary data obtained from the company's annual report. The internal auditor objectivity and audit committee independence were excluded from hypothesis testing, because they have constant values during the year of observation. Simultaneously the quality of internal auditors (experience, certification, training) and audit committee effectiveness (size, number of meetings, expertise) have a significant negative effect on corruption. Meanwhile, partially only the experience of internal auditors has a negative effect on corruption. Internal auditor certification, internal auditor training, audit committee size, number of audit committee meetings, and audit committee expertise have no effect on corruption.